The Four Exits of Senior High School: A Tracer Study - Kristhen Gonzaga; Zipporah Abegail Duyag; Nidine Dominese; Jennie Hyolim; Sydel Camille Compo (PT ARRUS Intelektual Indonesia, 2026)
Understanding the chosen exit paths of graduates is essential for evaluating the effectiveness of the SHS program and guiding future curriculum development. This study aims to trace the exit paths of senior high school graduates from a higher education institution in Ozamiz City, Misamis Occidental, focusing on their progression into tertiary education, employment, entrepreneurship, and middle-level skills development. The study employed a quantitative approach using a descriptive research design. Data were collected from 371 randomly selected graduates using questionnaires. The responses were analyzed using statistical techniques such as the T-test, mean, percentage, standard deviation, and frequency. The results reveal that most of the respondents were female, primarily aged between 20-21 years old, with a significant number coming from families earning less than 10,000 currency units. A majority of graduates pursued higher education, while a smaller portion engaged in employment, entrepreneurship, or middle-level skills development. The study found that the senior high school program was perceived as effective in preparing students for higher education and employment and most effective in fostering entrepreneurship. However, while the program is rated as effective in middle-level skills development, it receives the lowest rating among the constructs evaluated. Notably, no significant differences were found in the perceived effectiveness of the program when grouped according to profile. The senior high school program is generally effective in achieving its educational goals.